'Sampling' is freedom of art: The German Federal Constitutional Court deliberates on the acceptability of music sampling in the 'Metall auf Metall' case. Issue 6 (December 2017) - Zhang, Chenguo
Abstract: In the 'Metall auf Metall' case, the German Federal Constitutional Court recently deliberated the permissibility of sampling, an essential tool of musical borrowing in pop music production. The court reiterated that the freedom of art stipulated in Article 5, Paragraph 3 of the German Constitution requires that the 'sampling' of bits of sound recordings be recognized as artistic expression and creation instead of an infringement of rights. Thereby, the 'per se infringement rule' applied by the German Federal Supreme Court in this case (2013) was rejected. The note argues that more careful consideration must be given to the extent to which musical borrowing can and has been a source of innovation within the music industry. Copyright law must recognize and incorporate musical borrowing by developing commercial practices, such as 'sample clearing', for music that samples existing works in its creation. Moreover, the judiciary in Germany and the EU must endeavour to develop conventional practices to balance the interests of rights holders and users in disputes resulting from the challenges of modern digital technology to the traditional copyright framework with an enumerative and exhaustive list of copyright exception and limitation rules.